EDUCATION AS A TOOL FOR SOCIAL UPLIFTMENT: THE PIONEERING EFFORTS OF SHAHU MAHARAJA (International Journal of Food and Nutritional Sciences, 2021)
This research explores the educational reforms initiated by Shahu Maharaja in Kolhapur during the early 20th century. As a progressive ruler, Shahu Maharaja recognized education as a pivotal instrument for social upliftment and democratization. His efforts to provide free and compulsory primary education, alongside the establishment of numerous educational institutions, significantly contributed to the intellectual and social empowerment of marginalized communities. By promoting inclusive education and challenging the caste-based monopolies on knowledge, Shahu Maharaja aimed to eradicate the entrenched social inequalities and foster a more equitable society. This study examines the scope, impact, and legacy of his educational policies, highlighting how they served as a foundation for broader social and economic reforms in colonial India.